2022
DOI: 10.3390/cancers14194844
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Significance of Stromal Tumor-Infiltrating Lymphocytes (sTILs) in ER-Positive/HER2−Negative Postmenopausal Breast Cancer Patients

Abstract: The clinical impact of tumor-infiltrating lymphocytes (TILs) is less known for breast cancer patients with the estrogen receptor-positive (ER+)/human epidermal growth factor receptor-negative (HER−) subtype. Here, we explored the prognostic and predictive value of TILs regarding distant recurrence-free interval (DRFI) and breast cancer-specific survival (BCSS) in 763 postmenopausal patients randomized to receive tamoxifen vs. no systemic treatment. TILs were assessed in whole section tumor samples stained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Despite this, CD19-positive B cells have been observed to inhibit the aggressiveness of triple-negative breast cancer (TNBC) and the HER2-positive breast cancer subtype, extend patients' lifespans, and reinforce antitumor immunity. 16 Additionally, other studies have demonstrated that CD19(+) B cells prolong the life of those with muscle-invasive bladder cancer. 17 The part of CD19(+) tumor-infiltrating B cells in certain solid tumors is still a matter of contention.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, CD19-positive B cells have been observed to inhibit the aggressiveness of triple-negative breast cancer (TNBC) and the HER2-positive breast cancer subtype, extend patients' lifespans, and reinforce antitumor immunity. 16 Additionally, other studies have demonstrated that CD19(+) B cells prolong the life of those with muscle-invasive bladder cancer. 17 The part of CD19(+) tumor-infiltrating B cells in certain solid tumors is still a matter of contention.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, distant recurrence-free interval (DRFI) of patients treated with TAM was significantly improved compared with those with no TAM in ER + /HER2− postmenopausal breast cancer when TIL-low group (< 10%) was considered (HR 0.49, 95% CI 0.31–0.78, p = 0.002). But no significant benefit was obtained from TAM among patients with TIL-high group (≥ 10%) [ 12 ]. These data support the hypothesis that the inferior efficacy of ET in the TIL-high group of the ER + /HER2− subtype results in a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…CD19(+) B cells are identi ed as a signi cant factor in immune evasion from breast cancer due to their high tumor grade, ER-negative status, and expression of IL-10 and PD-L1. Despite this, CD19-positive B cells have been observed to inhibit the aggressiveness of triple-negative breast cancer (TNBC) and the HER2-positive BC subtype, extend patients' lifespans, and reinforce antitumor immunity (Pousette et al 2022). Additionally, other studies have demonstrated that CD19(+) B cells prolong the life of those with muscle-invasive bladder cancer (Jiang et al 2019).…”
Section: Introductionmentioning
confidence: 99%